Developments in the law on constitutional and statutory interpretation: Vellama d/o Marie Muthu v AG [2012] SGHC 155; [2013] SGCA 39 - ONG, Benjamin Joshua (Institutional Knowledge at Singapore Management University, 2013)
Following the expulsion of Mr Yaw Shin Leong, MP for Hougang Single MemberConstituency (SMC), from his party, the applicant in Vellama d/o Marie Muthu v AttorneyGeneral[2012] SGHC 155, [2012] 2 SLR 1033 (“Vellama (HC)”); [2013] SGCA 39 (“Vellama(CA)”), a resident of Hougang SMC, sought a declaration that the Prime Minister did nothave unfettered discretion in deciding whether and when to call a by-election to fill thevacant seat in Parliament, given that art 49(1) of the Constitution provides that “Wheneverthe seat of a Member, not being a non-constituency Member, has become vacant for anyreason other than a dissolution of Parliament, the vacancy shall be filled by election in themanner provided by or under any law relating to Parliamentary elections for the time beingin force.” This note focuses on this substantive issue rather than the procedural issues andissues of locus standi, which the courts also discussed at length.